2020
DOI: 10.1093/jisesa/ieaa091
|View full text |Cite
|
Sign up to set email alerts
|

Antixenosis, Antibiosis, and Potential Yield Compensatory Response in Barley Cultivars Exposed to Wheat Stem Sawfly (Hymenoptera: Cephidae) Under Field Conditions

Abstract: Wheat stem sawfly, Cephus cinctus Norton, is an economically serious pest of cereals grown in North America. Barley cultivars were previously planted as resistant crops in rotations to manage C. cinctus, but due to increasing levels of injury to this crop, this is no longer a valid management tactic in Montana. Therefore, we aimed to understand antixenosis (behavioral preference), antibiosis (mortality), and potential yield compensation (increased productivity in response to stem injuries) in barley exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
1
1
0
Order By: Relevance
“…We found a greater number of eggs per stem in 'Hockett' than in 'Craft' at both developmental stages (Table 3). Several previous studies have reported that 'Hockett' is preferred over 'Craft' by the number of eggs per stem (Varella et al 2018, Achhami et al 2020. Our results align with previously reported results that female prefers volatiles from susceptible cultivars and thus lays more eggs in wheat (Weaver et al 2009, Varella et al 2016) and now, in barley cultivars (Achhami et al 2020 a, b, c).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a greater number of eggs per stem in 'Hockett' than in 'Craft' at both developmental stages (Table 3). Several previous studies have reported that 'Hockett' is preferred over 'Craft' by the number of eggs per stem (Varella et al 2018, Achhami et al 2020. Our results align with previously reported results that female prefers volatiles from susceptible cultivars and thus lays more eggs in wheat (Weaver et al 2009, Varella et al 2016) and now, in barley cultivars (Achhami et al 2020 a, b, c).…”
Section: Discussionsupporting
confidence: 92%
“…Second, barley production in Montana is the third highest in the United States (US Department of Agriculture 2020) and barley is becoming a more common host to C. cinctus. Third, in the past, barley was described as a resistant crop to C. cinctus (Farstad and Platt 1946), but recent studies have reported that both infestation rate and larval survival rate in barley are in increasing (Varella et al 2018, Achhami et al 2020c. Therefore, the question arises does the ovipositing female display a similar host selection and oviposition behaviors as is known for wheat cultivars?…”
mentioning
confidence: 99%